Prosperity Gospel Redefined : The Impact of Charismatisation of the Mainline Churches in Tanzania - Ngoy, Leita, (Global Religion - Religion global ;, 2025)
This book provides an in-depth discussion of the cultural and missional implications of the explosion of charismatic Christianity on mainline denominations in Africa. The book proposes that the charismatization of mainline churches is a contextual, missional, and transcultural phenomenon that enriches and invigorates African Christian communities. Focused on the experience of the Evangelical Lutheran Church in Tanzania and using Prosperity Gospel as an example, the book explores how some mainline churches are being enriched by adopting practices of charismatic Christianity. It proposes a holistic and contextual understanding of the Prosperity Gospel, understood as the mafanikio gospel in Tanzania, as a relevant theological resource for Lutherans in Dar-es-Salaam. In doing so, it intends to contribute to the needed paradigm shift in theological discourses around Prosperity Gospel to challenge stereotypical criticisms that label it false and misleading.